Program Magang Berbasis Kearifan Lokal: Penguatan Literasi Numerasi Siswa SMP Swasta Cinta Rakyat 2 Pematangsiantar - Julianson Silitonga; Mungkap Mangampul Siahaan; Febri Crownika Tampubolon; Riris Amelia Sidauruk; Tias Bastian Saragih; Pika Marselli Simarmata; Yeni Desika Sinaga; Olivia Damanik (Getpress Management Journals, 2025)
This paper originates from a student internship program conducted as part of the implementation of the Merdeka Mengajar Curriculum at SMP Swasta Cinta Rakyat 2 Pematangsiantar. The study aims to describe the internship experience and analyze how local wisdom is utilized to strengthen students’ literacy and numeracy skills. Drawing on classroom observations, documentation of learning activities, interviews, and daily reflective journals, the study demonstrates that Rumah Bolon and the traditional game Marsitekka function as effective pedagogical media for stimulating students’ understanding of space, symbols, patterns, and combinatorial reasoning. The findings indicate that the integration of local wisdom not only enhances students’ attention and participation but also enriches their numeracy thinking through contextual and enactive learning experiences. Rumah Bolon strengthens cultural literacy while deepening mathematical understanding, whereas Marsitekka provides space for students to develop strategies, logic, and problem-solving skills spontaneously. Overall, the internship program affirms that integrating local wisdom to enhance cognitive aspects of literacy and numeracy within the Merdeka Curriculum framework is essential for meaningful learning.